MODEL PERILAKU KEPATUHAN ZAKAT: SUATU PENDEKATAN TEORI - Aulia Fuad Rahman, Zulkifli Daud, Sanep Ahmad, (Fakultas Ekonomi, UIN Maliki Malang, 2011)
Zakah is one of the religious orders that must be complied by every Muslim who had the capacity to do so. The level of such complience was affected by the faith factor. However, if payment of zakah was obliged through the formal institution of zakah collector, as that was applied in several islamic countries, then the zakah complience is now becomes the obedience against the formal institution of zakah collector. Therefore, the management of zakah institution, collecting efficiency and several other factors that were connected with the services given by zakah institution influenced the level of zakah complience. The study aimed at forming the zakah complience model of the formal institution of zakah collector. The model was formed based on the tax compliance model by adding several important factors that influenced the obedience of zakah payment. The availability of zakah complience model will benefit to facilitate research concerning the empirically test of zakah complience and evasion to the formal institution of zakah collector.